Abstract WP395: Mapping the Spatial Distribution of Neutrophils in a Murine Model of Ischemia/Reperfusion Injury - Schappell, Laurel; Madeira, Miguel; Tang, Meiyi; Tsirka, Stella; Nadkarni, Neil (Stroke (1970), 2025)
Introduction: Polymorphonuclear Neutrophils (PMNs) are the first blood-derived immune cells to respond in ischemia/reperfusion injury (I/RI). PMNs exhibit spatial heterogeneity and play complex roles in injury progression and resolution. However, preclinical studies investigating the immune response have been limited to studying the area of maximal infarction or highly representative images throughout the stroke hemisphere. As a result, the spatial relationships of PMNs in the acute stages of I/RI throughout the whole brain remain largely unknown. To address this gap in knowledge, we applied light sheet microscopy (LSM) to fully map the spatial patterns of PMNs in relation to neuronal injury throughout the murine brain in I/RI. Methods: The transient middle cerebral artery occlusion (tMCAO) model was used to recapitulate I/RI in a Ly6G-tdTomato transgenic mouse line expressing an endogenous fluorescent marker for PMNs. Mice were subject to 60 min or 90 min of ischemia to model strokes of varying severity. Whole brains were collected 72h post-tMCAO, (the point of maximal PMN infiltration), cleared, and then imaged using LSM. Brains were co-labeled with NeuN (neurons), registered, and parcellated according to the Allen Brain Atlas. Relationships of PMNs to the M1 segment of the MCA were then mapped. Results: Following 60 min tMCAO, PMNs infiltrated predominantly in infarcted regions of the cerebral cortex (NeuN Negative). Further, the density of PMNs was higher in anatomic regions supplied by the middle cerebral artery (MCA) and negatively correlated with the distance from the M1. In the 90 min tMCAO, PMN infiltration followed a similar pattern with PMN accumulation predominantly in the ischemic cortex and increased with proximity to the M1. However, PMN densities in the 90 min tMCAO were significantly higher than in the 60 min tMCAO. Additionally, PMN-rich regions in the 90 min tMCAO were more concentrated than in the 60 min tMCAO. Conclusions: Our data demonstrate that PMNs exhibit spatial heterogeneity following experimental stroke and cluster in regions corresponding to increased neuronal death and proximity to the MCA. PMN distribution was also influenced by the duration of ischemia, suggesting that PMNs are highly responsive to both stroke topology and severity. These data enable a more in-depth understanding of neutrophil dynamics in I/RI that can be leveraged to inform future stroke therapies directed at limiting the immune response.